Digital iCGPA Simulator - Aziman, Abdullah; Mukhlis, Mohamad; Farhah Nur Aina, Ghazali; Nur Alina, Ahmad Shuhaili; Nurul Saffinas, Maswi; Rubasri, Balamurali (Universiti Malaysia Pahang, 2016)
The introduction of iCGPA concept to highlight student and graduate talent is a Malaysia national agenda. It can be seen as a product of implementation of Malaysia Qualification Framework (MQF) that based on eight standard learning outcomes. To speed the adoption at the nation wide, effective mechanism to understand how it works is crucial. Digital simulator is one of effective way to allow user to understand the mechanism and how iCGPA works.